Pemuda, Perkawinan, dan Perubahan Sosial di Indonesia - Ariane Utomo; Oki Rahadianto Sutopo (Jurnal Studi Pemuda, 2020)
An examination into the changing patterns, meaning, norms, and discourses around marriage - in the context of transition to adulthood - offers a unique window to disentangle the complex processes of social change in post -Reformasi Indonesia. Among the many dimensions of social change affecting changing patterns of marriage and transition to adulthood include: globalization; demographic transition; trends in population mobility concerning migration and urbanization; economic uncertainties and inequality; and a series of contestation on norms around marriage and the family which has shadowed the political landscape post-Reformasi. How does such a complex process of social change shape the changing patterns and narratives on marriage? In particular, how do young people navigate the changing marriage patterns in the context of such complex, rapid, and massive social change? These two questions are pivotal to the current special issue in Jurnal Studi Pemuda. To provide context and highlights the contributions of the papers in this issue, this article reviews several dimensions and indicators of marriage and family change in Indonesia, and outlines their relation to the broader contexts of transition to adulthood and social change in the last two decades following Reformasi.